Technical Issues and Their Effect on the Financial and Time Scheduling of the Building Under Roof and/or Floor Upbuilding - Lámer, Géza (International Journal of Engineering and Management Sciences, 2018)
Building under roof and/or floor upbuilding raises technical issues different as one raise in the case of green investments. Primarily, depending of system of building constructions of the existing building there is a possibility to build under roof, and/or floor upbuilding. In the paper we review those technical issues, what decide, that in the case of given building there is or not possibility to build under roof, and/or floor upbuilding. We examine in general, that in the case of building under roof, and/or floor upbuilding what building process should be considered, and what kind of time and financial scheduling is advisable to prescribe. We will present a case study, that the inadequate processing of technical issues may require time and financial rescheduling.